Managing Weak Signals In The Foreign Economic Activity of a Modern Enterprise: Preventing a Decrease in the Financial and Economic Security with a Strategic Approach to Solving the Problem - Alkema, Viktor; Hryhoruk, Pavlo; Skhidnytska, Halyna; Senyk, Sviatoslav; Mykytyn, Oleh; Алькема, Віктор Григорович (Transnational Press London Ltd, 2024)
The main purpose of the article is to create a system for responding to weak signals in the foreign economic activity of a modern enterprise. The scientific task is to form models of response and management of weak signals in the foreign economic activity of a modern enterprise, in the context of preventing a decrease in the financial and economic security of the enterprise. The proposed approach is based on the use of methods of DFD and functional modeling. As a result, two key models were formed: the first is the main model of management decision-making in the system of responding to weak signals and the second is the management functions for responding to weak signals. Our research makes an innovative contribution by integrating DFD and functional modeling methodologies to develop comprehensive models that provide deeper and more effective understanding of managerial decision-making in the context of responding to weak signals in a dynamic foreign economic environment.
Keywords: enterprise; weak signals; threats; strategic planning; functional models; business environment; management